Análisis a los Estados Financieros en la Unidad de Negocio Lavadora y Lubricadora de la Cooperativa de Transportes Loja de la Ciudad de Loja, Período 2020-2021 - Vanegas Rodríguez, Johnny Patricio (2023)
The research work called: ANALYSIS OF THE FINANCIAL STATEMENTS OF THE BUSINESS AREA LAUNDRY AND LUBRICATING OF LOJA TRANSPORT COMPANY OF LOJA CITY, PERIOD 2020-2021 was developed with the purpose to demonstrate the acquired knowledge in practice, as well as to carry out the financial analysis of the Laundry and Lubricating Company to know the economic-financial situation of the Business Area, based on the variations observed in the different analysis techniques applied in the Laundry and Lubricating Transport Company of Loja, thus enabling conclusions and recommendations and, on the basis of these, the management and administrative take decisions. For the development of the degree work, it was necessary to use different methods in order to use the information gathered from the Laundry and Lubricating as financial statements and to conduct several interviews with the accountant to enable clarification of the results found in the vertical or horizontal analysis, as well as the financial indicators and thus to choose the most relevant points, beginning with the scientific method that allowed to find and classify the theoretical information which was key for the development of the practice; it was used the deductive and inductive methods which, both from the theoretical and the practical part, were used to get from general facts to the particular or most relevant facts and from them to give general conclusions; the mathematical method was used to visualize the percentages of the groups of accounts and solve the financial indicators and the statistical method to display these values for a better analysis and finally the analytical and synthetic methods which allowed to see the causes and effects of the findings and give the conclusions and recommendations presented in a financial report for the managers and administrators of the Laundry and Lubricating Area to take the best decisions.